Analisis Faktor-Faktor Yang Mempengaruhi Minat Menggunakan Mobile Banking - alfinaeka; batara daniel bagana (Universitas Sains dan Teknologi Komputer, 2022)
Research was conducted to analyze factors that affect interest in using Mobile Banking. Research conducted on the use of Wow Aps in central Java using the Technology Acceptance Model (TAM) theory developed by Fred Davis in 1989 which was later updated by Davis and Venkatesh in 1996. It was a theory that was often used by researchers regarding public confidence in new technology and acceptance of technology. Sampling method used convenience sampling method. The data collection technique used by researchers was questionnaire deployments aimed at users of the Wow Aps Mobile Banking application located in central Java as respondents. Relationships and/or influences between variables were described using multiple regression analysis methods. The results of the analysis of this study stated that the perceived usefullness, the Perceived Ease of Use, the Feature Availability has a significant effect on Behavioral Intention to Use .